Styryl-based new organic chromophores bearing free amino and azomethine groups: synthesis, photophysical, NLO, and thermal properties - Putra, Anka Utama; Çakmaz, Deniz; Seferoğlu, Nurgül; Barsella, Alberto; Seferoğlu, Zeynel (Beilstein Journal of Organic Chemistry, 2020)
Herein we report the synthesis and characterization of a new series of styryl-based push-pull dyes containing a free amino group and their Schiff base derivatives. The dyes include the dicyanomethylene group as an acceptor and different para-substituted alkylamines as donors. Morever as a proton-sensitive group a pyridin-2-yl substituent was attached to the para-position of the phenyl moiety in both series of compounds. The photophysical properties of the dyes were examined in various solvents with different polarities and showed absorption in the visible region and green-red emission with low quantum yields. The absorption and the emission maxima were shifted bathocromically by increasing the solvent’s polarity. However, there was no correlation with the polarity parameters of the solvents. The pH-sensitive properties of all prepared Schiff bases were examined against TBAOH in DMSO, via deprotonation of the OH group in the salicylidene moiety and their reverse protonation was also investigated using TFA. The Schiff bases exhibited a bathochromic shift upon the addition of TBAOH to their solutions in DMSO. Therefore, they showed potential to be utilized as colorimetric and luminescence pH sensors. The second-order nonlinear optical (NLO) responses of the dyes were measured by the electric field-induced second harmonic (EFISH) generation method. The highest μβ values were obtained for the dyes bearing the julolidine donor as 1430 × 10−48 esu (for free amino derivative) and 1950 × 10−48 esu (for Schiff base derivative), respectively. The structural and electronic properties of the dyes as well as their NLO properties were further studied using DFT calculations. The thermal stabilities of all dyes were evaluated by thermogravimetric analysis (TGA). The TGA data showed that all dyes were thermally stable up to 250 °C.
Keywords: DFT calculations; NLO; pH sensitive dyes; Schiff base; solvent effect; styryl dyes

Molecular Fluorescence: Principles and Applications - Valeur, B.; Berberan-Santos, M. N. (Wiley-VCH, 2012)

Spectrophotometry and Spectrofluorimetry: A Practical Approach - Gore, M. (Oxford University Press, 2000)

(untitled) - Braslavsky, S. E. (Pure Appl. Chem., 2007)

(untitled) - Williams, D. J. (Angew. Chem., Int. Ed. Engl., 1984)

Nonlineaer Optics - Boyd, R. W. (Academic Press, 2003)

(untitled) - Marder, S. R.; Beratan, D. N.; Cheng, L.-T. (Science, 1991)

(untitled) - Eaton, D. F. (Science, 1991)

(untitled) - Deng, G.; Xu, H.; Huang, H.; Jiang, J.; Kun, J.; Zhang, X.; Li, Z.; Liu, J. (J. Mol. Struct., 2019)

(untitled) - Deng, G.; Xu, H.; Kuang, L.; He, C.; Li, B.; Yang, M.; Zhang, X.; Li, Z.; Liu, J. (Opt. Mater., 2019)

(untitled) - Liu, J.; Ouyang, C.; Huo, F.; He, W.; Cao, A. (Dyes Pigm., 2020)

(untitled) - Liu, J.; Gao, W.; Kityk, I. V.; Liu, X.; Zhen, Z. (Dyes Pigm., 2015)

(untitled) - Achelle, S.; Barsella, A.; Baudequin, C.; Caro, B.; Robin-le Guen, F. (J. Org. Chem., 2012)

(untitled) - Klikar, M.; le Poul, P.; Růžička, A.; Pytela, O.; Barsella, A.; Dorkenoo, K. D.; Robin-le Guen, F.; Bureš, F.; Achelle, S. (J. Org. Chem., 2017)

(untitled) - Achelle, S.; Kahlal, S.; Barsella, A.; Saillard, J.-Y.; Che, X.; Vallet, J.; Bureš, F.; Caro, B.; Guen, F. R.-l. (Dyes Pigm., 2015)

(untitled) - Kreuer, K.-D. (Chem. Mater., 1996)

(untitled) - Cukierman, S. (Biochim. Biophys. Acta, Bioenerg., 2006)

(untitled) - Wraight, C. A. (Biochim. Biophys. Acta, Bioenerg., 2006)

(untitled) - Czarnik, A. W. (Chem. Biol., 1995)

(untitled) - Yan, N. D. (Can. J. Fish. Aquat. Sci., 1983)

(untitled) - Gerloff-Elias, A.; Spijkerman, E.; Pröschold, T. (Plant, Cell Environ., 2005)

(untitled) - Lee, K. H.; Lee, H.-Y.; Lee, D. H.; Hong, J.-I. (Tetrahedron Lett., 2001)

(untitled) - Agmon, N.; Bakker, H. J.; Campen, R. K.; Henchman, R. H.; Pohl, P.; Roke, S.; Thämer, M.; Hassanali, A. (Chem. Rev., 2016)

(untitled) - Fayed, T.; El-Morsi, M.; El-Nahass, M. (J. Chem. Sci., 2013)

(untitled) - Achelle, S.; Rodríguez-López, J.; Katan, C.; Robin-le Guen, F. (J. Phys. Chem. C, 2016)

(untitled) - Chemchem, M.; Yahaya, I.; Aydıner, B.; Seferoğlu, N.; Doluca, O.; Merabet, N.; Seferoğlu, Z. (Tetrahedron, 2018)

(untitled) - Wencel, D.; Abel, T.; McDonagh, C. (Anal. Chem. (Washington, DC, U. S.), 2014)

(untitled) - Wu, D.; Sedgwick, A. C.; Gunnlaugsson, T.; Akkaya, E. U.; Yoon, J.; James, T. D. (Chem. Soc. Rev., 2017)

(untitled) - Fang, M.; Adhikari, R.; Bi, J.; Mazi, W.; Dorh, N.; Wang, J.; Conner, N.; Ainsley, J.; Karabencheva-Christova, T. G.; Luo, F.-T.; Tiwari, A.; Liu, H. (J. Mater. Chem. B, 2017)

(untitled) - Chiannilkulchai, N.; Driouich, Z.; Benoit, J. P.; Parodi, A. L.; Couvreur, P. (Sel. Cancer Ther., 1989)

(untitled) - Wang, J.; Xia, S.; Bi, J.; Zhang, Y.; Fang, M.; Luck, R. L.; Zeng, Y.; Chen, T.-H.; Lee, H.-M.; Liu, H. (J. Mater. Chem. B, 2019)

(untitled) - Yalçın, E.; Achelle, S.; Bayrak, Y.; Seferoğlu, N.; Barsella, A.; Seferoğlu, Z. (Tetrahedron Lett., 2015)

(untitled) - Çatal, E.; Keleş, E.; Seferoğlu, N.; Achelle, S.; Barsella, A.; Robin le Guen, F.; Seferoğlu, Z. (New J. Chem., 2018)

(untitled) - Bardasov, I. N.; Alekseeva, A. U.; Chunikhin, S. S.; Shishlikova, M. A.; Ershov, O. V. (Tetrahedron Lett., 2019)

(untitled) - Sztanke, K.; Maziarka, A.; Osinka, A.; Sztanke, M. (Bioorg. Med. Chem., 2013)

(untitled) - Di Bella, S.; Fragalà, I.; Ledoux, I.; Diaz-Garcia, M. A.; Marks, T. J. (J. Am. Chem. Soc., 1997)

(untitled) - Reimann, M. J.; Salmon, D. R.; Horton, J. T.; Gier, E. C.; Jefferies, L. R. (ACS Omega, 2019)

(untitled) - Berhanu, A. L.; Gaurav; Mohiuddin, I.; Malik, A. K.; Aulakh, J. S.; Kumar, V.; Kim, K.-H. (TrAC, Trends Anal. Chem., 2019)

(untitled) - Reichardt, C. (Chem. Rev., 1994)

(untitled) - Tydlitát, J.; Achelle, S.; Rodríguez-López, J.; Pytela, O.; Mikýsek, T.; Cabon, N.; Robin-le Guen, F.; Miklík, D.; Růžičková, Z.; Bureš, F. (Dyes Pigm., 2017)

(untitled) - Cvejn, D.; Achelle, S.; Pytela, O.; Malval, J.-P.; Spangenberg, A.; Cabon, N.; Bureš, F.; Robin-le Guen, F. (Dyes Pigm., 2016)

(untitled) - Le Droumaguet, C.; Sourdon, A.; Genin, E.; Mongin, O.; Blanchard-Desce, M. (Chem. – Asian J., 2013)

(untitled) - Fonseca, R. D.; Vivas, M. G.; Silva, D. L.; Eucat, G.; Bretonnière, Y.; Andraud, C.; De Boni, L.; Mendonça, C. R. (J. Phys. Chem. C, 2018)

(untitled) - Erande, Y.; Kothavale, S.; Sreenath, M. C.; Chitrambalam, S.; Joe, I. H.; Sekar, N. (Dyes Pigm., 2018)

(untitled) - Hoffert, K.; Durand, R. J.; Gauthier, S.; Robin-le Guen, F.; Achelle, S. (Eur. J. Org. Chem., 2017)

(untitled) - Denneval, C.; Achelle, S.; Baudequin, C.; Robin-le Guen, F. (Dyes Pigm., 2014)

(untitled) - Bergen, A.; Granzhan, A.; Ihmels, H. (Photochem. Photobiol. Sci., 2008)

Principles of Fluorescence Spectroscopy - Lakowicz, J. R. (Protein Fluorescence, 1983)

Digital Encyclopedia of Applied Physics - Valeur, B. (Molecular Fluorescence, 2009)

Solvatochromism - Suppan, P.; Ghoneim, N. (Royal Society of Chemistry, 1997)

(untitled) - Coelho, F. L.; de Ávila Braga, C.; Zanotto, G. M.; Gil, E. S.; Campo, L. F.; Gonçalves, P. F. B.; Rodembusch, F. S.; da Silveira Santos, F. (Sens. Actuators, B, 2018)

(untitled) - Hu, J.; Xia, B.; Bao, D.; Ferreira, A.; Wan, J.; Jones, G.; Vullev, V. I. (J. Phys. Chem. A, 2009)

(untitled) - Schäfer, K.; Ihmels, H.; Bohne, C.; Valente, K. P.; Granzhan, A. (J. Org. Chem., 2016)

(untitled) - Hansch, C.; Leo, A.; Taft, R. W. (Chem. Rev., 1991)

(untitled) - Lindner, E.; Zwickl, T.; Bakker, E.; Lan, B. T. T.; Tóth, K.; Pretsch, E. (Anal. Chem. (Washington, DC, U. S.), 1998)

(untitled) - Hisamoto, H.; Tsubuku, M.; Enomoto, T.; Watanabe, K.; Kawaguchi, H.; Koike, Y.; Suzuki, K. (Anal. Chem. (Washington, DC, U. S.), 1996)

(untitled) - Safavi, A.; Bagheri, M. (Sens. Actuators, B, 2003)

(untitled) - Ulrich, G.; Barsella, A.; Boeglin, A.; Niu, S.; Ziessel, R. (ChemPhysChem, 2014)

(untitled) - Singer, K. D.; Garito, A. F. (J. Chem. Phys., 1981)

(untitled) - Levine, B. F.; Bethea, C. G. (Appl. Phys. Lett., 1974)

(untitled) - Ledoux, I.; Zyss, J. (Chem. Phys., 1982)

(untitled) - Thami, T.; Bassoul, P.; Petit, M. A.; Simon, J.; Fort, A.; Barzoukas, M.; Villaeys, A. (J. Am. Chem. Soc., 1992)

(untitled) - Hu, C.; Liu, F.; Zhang, H.; Huo, F.; Yang, Y.; Wang, H.; Xiao, H.; Chen, Z.; Liu, J.; Qiu, L.; Zhen, Z.; Liu, X.; et al. (J. Mater. Chem. C, 2015)

(untitled) - Britton, H. T. S.; Robinson, R. A. (J. Chem. Soc., 1931)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Becke, A. D. (J. Chem. Phys., 1992)

(untitled) - Cossi, M.; Barone, V. (J. Chem. Phys., 2001)

(untitled) - Bauernschmitt, R.; Ahlrichs, R. (Chem. Phys. Lett., 1996)

Gaussian 09, Revision C.01 (Gaussian, Inc., 2010)